Practices Of Banks For Credits To Be Granted To Sme’s - Çetiner, Emine Müge; Acar, Cem Sadık (My University, 2020)
While a certain definition has not been made for SMEs across the world yet, this definition is determined according to conditions of country where SME operates in. In general, companies defined as SME constitute 80%-90% of the overall economy, SMEs lead and drive both employment and economy. In this study, definition of SMEs made in general or by banks and challenges and advantages to be seen with BASEL III are addressed. Innovations brought by BASEL III and effects of these innovations on SMEs are also mentioned. With a field study conducted for Istanbul province specifically, it is aimed to research the source of financing issues of SMEs and tools they use to get over this problem, possible problems they may face with BASEL III and their thoughts on the transition process. In the light of survey findings, it is concluded that most of enterprises operate as SME clients in Turkey, they go through financial issues and their concerns mostly focus on credit costs with BASEL III, but most of them expect a trouble-free transition to BASEL III.

KOBİ’lerin dünya genelinde kesin bir tanımı bulunmamakla birlikte faaliyet gösterdiği ülkenin şartlarına göre bu belirlenmektedir. Genellikle KOBİ tanımı içinde bulunan firmaların genel ekonominin %80-%90 oluşturmakla birlikte hem istihdamın hem de ekonomin öncüleri ve sürükleyicileri pozisyonundadırlar. Bu çalışmada, KOBİ’lerin genel tanımları ve Ülkemizdeki bankalarca yapılmış tanımları ve BASEL III ile birlikte karşılaşacakları zorluklar ve kolaylıklar ele alınmıştır. BASEL III getirdiği yenilikler ve bunların KOBİ’ler üzerinde etkilerinden bahsedilmiştir. İstanbul ili özelinde yapılan bir alan çalışması ile KOBİ’lerin finansman sorunlarının kaynağını ve bu sorunu aşmada kullandıkları araçları; BASEL III ile birlikte karşılaşmaları muhtemel sorunları ve geçiş süreçlerini hakkındaki düşüncelerini araştırmak amaçlanmıştır. Anket bulguları ışığında işletmelerin çoğunun Ülkemizde bulunan KOBİ segmet müşteriler içinde faaliyetini sürdürdüğünü, finansman sorununun yaşandığı ve BASEL III ile birlikte en çok kredi maliyetleri konusunda kaygı yaşadıkları ama çoğunun BASEL III’e sorunsuz bir geçiş beklediği sonucuna ulaşılmıştır.
Keywords: Basel iii; Banking; Istanbul province; KOBİ; Bankacılık; İstanbul ili; SMEs